Enhancement of the combustion, performance and emission characteristics of spirulina microalgae biodiesel blends using nanoparticles. (15th January 2022) - Ge, Shengbo; Brindhadevi, Kathirvel; Xia, Changlei; Salah Khalifa, Amany; Elfasakhany, Ashraf; Unpaprom, Yuwalee; Doan, Hien Van
Graphical abstract: Highlights: Spirulina microalgae blends were tested for performance and emission characteristics. Influence of Al2 O3 examined along with 15% and 30% microalgae blends. Increasing the concentration showed the contrary effects of the Brake thermal efficient. Addition of the nanoparticles stimulates the emission of NOx. Abstract: Over the past few years, the interest and need for an alternative fuel have been increasing and the biofuels are proved to the better fuel. The main objective of the paper is to improve the performance and emulsion characteristics of the biodiesel extracted from spirulina microalgae by adding little dosage of nanoparticles as a catalyst for the improved performance overall. The nanoparticles taken for the research was Al2 O3 from metallic nanoparticles group. All the tests were conducted in CI diesel engine at different load conditions such as 25%, 50%, 75% and 100% load. The fuel blends used are B0(Diesel 100%), B15 (15% spirulina biofuel + 85% diesel), B15 (15% spirulina biofuel + 85% diesel- 75 ppm Al2 O3 ), B30 (30% spirulina biofuel + 70% diesel), and B30 (30% spirulina biofuel + 70% diesel- 75 ppm Al2 O3 ) and with all biofuel blends and with pure diesel, 75 ppm Al2 O3 nanoparticles were sonicated to estimate the combustion performance and emission characteristics. From results, it is found that the nanoparticles added B15 biodiesel reduced the harmful gas emission while increased the combustion qualities. With regard to the engine performance, the fuel B15N and B30N reported higher BTE compared to B15 and B30. Further, the B15N reported reduced fuel consumption than other blends.